Problems of Preaching in Preventing Debt Behavior to Loan Sharks: Analysis of Challenges and Opportunities - M. Fiqri Alwan Dzaki; Rubino Rubino (Suluah Pasaman, 2026)
This study aims to analyze the problems of da'wah in dealing with debt to loan sharks in Tumpatan Village, Beringin District. This phenomenon shows that although the practice of usury is prohibited in Islamic teachings, some people still use the services of loan sharks to meet urgent economic needs. This study uses a qualitative approach with a case study type to understand the dynamics of da'wah in the social context of society. Data were collected through in-depth interviews, observation, and documentation involving religious leaders, mosque administrators, and the local community. The results show that the problems of da'wah in dealing with debt to loan sharks are related to three main elements of da'wah: mad'u, da'wah methods, and da'wah materials. Community participation in religious study activities is still low with an attendance rate of around five percent of the total community. Furthermore, the da'wah methods used are still normative and mostly use lectures without a solution-oriented approach to the community's economic problems. Da'wah materials also focus more on ritual worship and rarely discuss muamalah issues such as the prohibition of usury. These findings contribute to the development of Islamic da'wah and communication studies by showing the relationship between da'wah activities, the socio-economic conditions of the community, and the practice of loan sharks in the context of rural communities.